(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
The paper presents basic energy characteristics of wood pellets from different producents. We took the samples from producents in Bulgaria and in Slovakia. Energy characteristics of the pellets, such as their dimensions, moisture content, content of ash, gross and net calorific value were estimated in accordance with European technical standards. We used the standard STN EN 14961-1:2010, Solid biofuels as a basic platform for estimation. Values of net calorific value belonged to interval between 16,103 MJ.kg-1 and 17,120 MJ.kg-1, moisture content values were in interval 7,2÷12 %. We observed ash content of the samples from 0,43 to 1,47 %. All of tested samples met the requirements of the standards for ecological biofuel.